Completeness of digital accessible knowledge of plants of Benin and priorities for future inventory and data discovery - GANGLO, COSSI JEAN; KAKPO, Sunday Berlioz (My University, 2016)
Discovery of and access to primary biodiversity data are critical components in informed decision-making regarding sustainable use of biological resources and conservation of biodiversity. Primary biodiversity data are increasingly available from Benin, but information about completeness of this information across the country is still lacking for most groups. This study analyzed the Digital Accessible Knowledge regarding the plants of Benin to identify gaps in both geographic and environmental dimensions. Many gaps exist in plant data for Benin, particularly in the northern most departments; central and southern Benin are better known, but some gaps remain even there. The resulting view of Beninese Digital Accessible Knowledge can guide future inventory and data discovery efforts
Keywords: Benin; inventory completeness; data cleaning; digital accessible knowledge; gaps; GBIF